Fabrication of Tween-20 coated PVDF membranes for wastewater treatment: optimization of preparation parameters, removal and membrane fouling control performance. Issue 35 (27th June 2019) - Wu, Daoji; Zhou, Weiwei; Cheng, Xiaoxiang; Luo, Congwei; Li, Peijie; Zhang, Fengzhi; Ren, Zixiao
Abstract : In the present study, polyoxyethylene (20) sorbitan monolaurate (Tween-20) was employed as a surface coating agent for hydrophilic modification of poly(vinylidene fluoride) microfiltration membranes. Abstract : In the present study, polyoxyethylene (20) sorbitan monolaurate (Tween-20) was employed as a surface coating agent for hydrophilic modification of poly(vinylidene fluoride) microfiltration membranes. The optimized parameters for membrane preparation ( i.e., coating temperature, coating concentration, coating time and drying time) were systematically investigated. Contact angle and transmembrane pressure were employed to evaluate the efficiency of the modified membranes, and the optimized parameters were proposed. The removal of chemical oxygen demand (COD) and suspended solids (SS), as well as fouling control performance, was further evaluated. The results showed that the optimized parameters were 40 °C, 4.5 mmol L −1, 45 min and 45 min for coating temperature, coating concentration, coating time and drying time, respectively. Under these conditions, a hydration layer on the surface was formed, resulting in a more hydrophilic membrane surface. During domestic wastewater treatment in membrane bioreactor (MBR), the Tween-20 modified membrane exhibited better performance with rejection efficiencies of 94.56% and 97.53% for COD and SS, respectively. Tween-20 coating could mitigate the increase of transmembrane pressure and reduce the concentration of proteins accumulated on the membrane surface, which was effective for membrane fouling control. Simultaneously, the operation time of MBR was extended from 25 to 46 days. Furthermore, the stability of Tween-20 coated PVDF membrane was also verified. The results indicated that surface coating with Tween-20 is efficient and easy to be carried out, showing a great potential for application in MBR during wastewater treatment.